Fuzzy mathematical models in the tasks of evaluation of scientific and pedagogical personnel activity effectiveness aimed at creation of the educational and methodical basis for realization of distant education technology - Mokin, B. I.; Mokina, Yu. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Fuzzy mathematical models have been adapted to conditions of evaluation of various forms of educational and methodical activity performed by scientific and pedagogical staff of the university. Criteria have been determined, the technique has been developed aimed at evolution of various forms of educational and methodic activity of the staff, which can be applied in the process of realization of distant education technology.